Limno-chemical parameters vis-a-vis productivity in Pong reservoir, Himachal Pradesh - KAUSHAL, D K; KUMAR, S; GOPALAKRISHNAYYA, C H (The Indian Journal of Animal Sciences, 2014)
Pong reservoir (15000 ha) in Himachal Pradesh, was assessed during August 1991 to July 1992 for its limno-chcmical features and productivity status. Total alkalinity (48 to 96 ppm), temperature (13 to 31Â°C), pH (7.1 to 8.3) and specific conductivity (96.4 to 195.8 umhos/cm-l) mdicated medium productivity. The values of chemical parameters were generally high during summer and showed decline dunng monsoon period. The reservoir exhibited thermal and biogenic chemical stratification in respect of oxygen, bicarbonate and specific conductivity. The annual carbon production was to the tune of 93725 tonnes or 6248 kg/hal annum. The conversion ratio of gross carbon to fish (496 t) was 0.23% in this reservoir. The reservoir could be developed for increasing yield if better management norms are adopted.